KLENTENG SUMBER NAGA SEBAGAI TEMPAT IBADAH TRI DHARMA DI DESA MANGUNHARJO, MAYANGAN, PROBOLINGGO SEJARAH, DAN POTENSINYA SEBAGAI SUMBER BELAJAR SEJARAH DI SMA - Wafi, Abdul; Maryati, Tuty; Martayana, Putu Hendra Mas (Widya Winayata : Jurnal Pendidikan Sejarah, 2025)
This study aims to: 1) Explain the history of the establishment of Sumber Naga Temple as a TriDharma place of worship in Probolinggo, and 2) Explore the function of Sumber Naga Temple as apotential source for history learning in senior high schools. The researcher employed historicalresearch methods in this study. Data were collected through observation, interviews, and documentanalysis. The findings of the study indicate that: 1) The history of Sumber Naga Temple inProbolinggo officially began in the 4th year of Tongzhi (1865), founded by Wen Baochang, the brotherof Wen Yuanchang, along with several members of the Han family and 172 registered donors. 2)Sumber Naga Temple holds potential as a source of historical learning for the community, teachers,and students. It also broadens understanding of architectural development, the temple’s charactereducation values, local history, and the influence of Tri Dharma temples on the Chinese ethniccommunity in East Java.